Stochastic processes govern gut bacterial community assembly in a Schistosoma mansoni-transmitting snail, Biomphalaria straminea. - Zhanhong Yuan; Jinni Hong; Jehangir Khan; Jinghuang Lu; Benjamin Sanogo; Zhongdao Wu; Xi Sun; Datao Lin (PLoS Neglected Tropical Diseases)
Background Studies have revealed extensive taxonomic classifications and patterns of gut microbial diversity in snails, with limited focus on community assembly processes. To better understand the balance between stochastic and deterministic processes in the snail gut microbial assembly and their associations with snail fitness, we used the freshwater snail Biomphalaria straminea as a model and analyzed the gut bacterial communities from 118 samples via high-throughput sequencing of the 16S rRNA gene. Results This study reveals that Proteobacteria and Bacteroidota dominate the gut microbiota of B. straminea. Snails from different laboratory habitats exhibit similar gut bacterial diversity but significantly different community structures. The assembly of gut bacterial communities in both laboratory and wild samples is predominantly influenced by stochastic processes rather than deterministic processes, as evidenced by the neutral community model (NCM). Furthermore, during the snail invasion and adaptation to a new environment, stochastic processes are more crucial than deterministic ones in shaping the snail gut microbiota. This indicates that the interplay between stochastic and deterministic processes in the snail gut microbial assembly is associated with host fitness during snail adaptation to a new environment. Based on the null model analysis, we also found that stochastic processes (based on dispersal limitation, homogenizing dispersal, and undominated processes) play a larger role than deterministic (based on homogeneous selection and variable selection) in driving the snail gut bacterial community assembly. Furthermore, the significant difference in the proportions of dispersal limitation and undominated processes is linked to both adaptive and non-adaptive snails. Conclusions This study demonstrates that stochastic processes govern the assembly of the gut microbiota in B. straminea. Furthermore, snail adaptation is associated with the interplay between stochastic and deterministic processes in gut microbial composition. This study provides a better understanding of the dynamic patterns of the gut microbial community in freshwater gastropods and may contribute to the development of strategies for controlling intermediate hosts and schistosomiasis.